AIDS DISEASE - Xaknazarova Dilorom Turaevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: Acquired Immunodeficiency Syndrome (AIDS) is a chronic, potentially life-threatening condition caused by the Human Immunodeficiency Virus (HIV). This article explores the historical development, transmission, prevention, and treatment of AIDS, while highlighting its impact on public health globally. Special attention is paid to recent advances in treatment, challenges in managing the epidemic, and societal responses to the disease. The study combines a review of relevant literature, methods of analysis, and findings to propose strategic solutions for combating AIDS.